PROBLEMA PIDANA MATI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DALAMSISTEM HUKUM INDONESIA - Mahmud, Ade (UI Scholars Hub, 2021)
The polemic ofcapitalpunishment inthe Indonesian legal system has long reaped a contra cons that never ends. People who oppose capital punishment have reasoned because this criminal is inhumane and ineffective, capital punishment is considered counter productive withthe aimof punishment, especially in overcoming the problem of illicit drug trafficking. That is why most European countries have decided to abolish capital punishment for all forms of crime, but developing countries, including Indonesia, still maintain it because it is seenas a form of punishment worthy of dealing with serious crimes. The discussion on capital punishment cannot be separated from the issue of basic human rights, especially the rights to life protected by the constitution, while on the other hand,the perpetrators of narcotics crimes deserve to be sentenced to death because they have disturbed the stability of a countrys security, threatened thenations generation and caused victims socially and economically.